2016
DOI: 10.1186/s13613-016-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Trials in adult critical care that show increased mortality of the new intervention: Inevitable or preventable mishaps?

Abstract: Several promising therapies assessed in the adult critically ill in large, multicenter randomized controlled trials (RCTs) were associated with significantly increased mortality in the intervention arms. Our hypothesis was that there would be wide ranges in sponsorship (industry or not), type(s) of intervention(s), use of DSMBs, presence of interim analyses and early stopping rules, absolute risk increase (ARI), and whether or not adequate prior proof-of-principle Phase II studies were done of RCTs that found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Corticosteroids are recommended only when septic shock cannot be corrected with adequate fluid resuscitation and vasopressors. [98] Antibodies against IL-6 have become effective drugs for the treatment of COVID-19. Tocilizumab, an IL-6 receptor antagonist, reduces the risk of progression to severe ARDS.…”
Section: Immunotherapymentioning
confidence: 99%
“…Corticosteroids are recommended only when septic shock cannot be corrected with adequate fluid resuscitation and vasopressors. [98] Antibodies against IL-6 have become effective drugs for the treatment of COVID-19. Tocilizumab, an IL-6 receptor antagonist, reduces the risk of progression to severe ARDS.…”
Section: Immunotherapymentioning
confidence: 99%
“…The researches of immunomodulatory therapy in sepsis have been going on for decades, and countless anti-inflammatory and immune-enhanced drugs have been tried, but the vast majority have become passers-by, so far no one obtained solid support by enough evidences and to be unanimously accepted by clinicians. 32 , 33 In the surviving sepsis campaign guidelines, immunotherapy is really in a blank state, 34 including its latest version of the anti-COVID-19 guideline. 35 In China, there is also no specific item of immunomodulatory therapy in the COVID-19 diagnosis and treatment protocol (trial version 7) released by the National Health Commission (NHC).…”
Section: Immunomodulatory Therapymentioning
confidence: 99%
“…Once the hypotension was corrected, corticosteroid was required to discontinue. 33 A meta-analysis published in 2018 also concluded that though the duration of shock, mechanical ventilation and intensive care unit (ICU) stay are reduced, the short- and longer-term mortality are unaffected and adverse events increased regarding septic shock treated with low dose corticosteroids. 40 More impressive, a survey of more than 1.5 million out-of-hospital users of prednisone showed that even in short-term (5–7 days) and with low-dose (17.5–20 mg/d) of oral prednisone, the incidence rate of fractures, venous thrombosis and sepsis were still very high.…”
Section: Immunomodulatory Therapymentioning
confidence: 99%
“…Randomised controlled trials often use objective measures which, although they may correlate with patient benefit and are easier to analyse statistically, ultimately do not matter to patients. Indeed, there are several examples in critical care where targeting objective measures has led to increased harm . From the orthopaedic literature, where the vast majority of work related to PROMs has been carried out, there is evidence that, although subjective measures do not always correlate with objective measures, patient satisfaction does .…”
Section: Objective or Subjective Outcomes – Which Ones Should We Be Mmentioning
confidence: 99%